Pengaruh Indeks Harga Konsumen terhadap Inflasi di Kota Medan Sumatera Utara Tahun 2024 - Silvia Diva Sari; Joy Stevani Simangunsong; Novita Sari Siboro (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to analyze the effect of the Consumer Price Index (CPI) on the inflation rate in Medan City during 2024. Inflation is a key macroeconomic indicator for assessing regional economic stability, and CPI serves as the primary tool to monitor changes in the prices of goods and services consumed by households. This research employs a quantitative approach using monthly time series secondary data sourced from the Central Statistics Agency and Bank Indonesia. The analysis techniques include classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) and simple linear regression. The results show that partially, CPI has no significant effect on inflation, with a significance value of 0.136. Simultaneously, the variables also show no significant influence, although the R² value of 18.8% indicates that CPI can explain a small portion of the variation in inflation. These findings suggest that other factors beyond CPI may play a more dominant role in influencing inflation in Medan City. The implications of this study are expected to provide input for local government in formulating more comprehensive inflation control policies based on more relevant macroeconomic variables.